Композиційно-номінативні логіки з непрямим іменуванням - Rossada, T.V.; Shkilniak, О.С. (Інститут програмних систем НАН України, 2015)
We construct sequent calculi for first-order composition-nominative logics of partial single-valued, total multiple-valued and partial multi-ple-valued quasi-ary predicates of quantifier level. The defined calculi are proposed for a general case of logics of quasi-ary predicates, for logics of single-valued equitone predicates and for logics of total multiple-valued antytone predicates. For the introduced calculi soundness and completeness theorems are proved.